Best Answer

(x+y) is the same as x+y

3(x+y) is 3 times as much. You multiply both x and y with 3 = 3x+3y

3(2x+4y) is the same as 3*2x+3*4y = 6x+12y

This is the general start of how to "solve" and do calculations with parentheses.

I am sure other people can add more examples with higher difficulty

Regards.

Q: How do you solve parentheses?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

solve the top and bottom first, as if each were in parentheses. Then Divide the numerator by the denominator

You square the number in the parentheses.

Parentheses are the following symbols: ( & ). These are parentheses. These help to do equations for example : 3+2x3=9 u are to put the parentheses or the backetts or the {} to help solve the equation so this is the way to put them in : 3+(2x3)=9. Hope This Helps!

18=3(3x-6)

you use PEMDAS which is parentheses exponents multiplication and division from left to right addition and subtraction from left to right

Related questions

Parentheses is when you are doing an equation, and you solve the problem.

solve the top and bottom first, as if each were in parentheses. Then Divide the numerator by the denominator

You square the number in the parentheses.

Parentheses are the following symbols: ( & ). These are parentheses. These help to do equations for example : 3+2x3=9 u are to put the parentheses or the backetts or the {} to help solve the equation so this is the way to put them in : 3+(2x3)=9. Hope This Helps!

understand, plan, solve,& check

18=3(3x-6)

It means you have to solve the problem in parentheses first. ex: 2X4+5= 13; 2X (4+5) = 18. The answer is different because you have to solve the problem in the Order of Operations. 1) Parentheses 2) Exponents like 22 3) Multiplication 4) Division 5) Addition 6) Subtraction PEMDAS or Please Excuse My Dear Aunt Sally.

you use PEMDAS which is parentheses exponents multiplication and division from left to right addition and subtraction from left to right

3(x+2) = x -18 3x+6 = x -18 3x -x = -18 -6 2x = -24 x = -12

Binomial Expansion makes it easier to solve an equation. It brings an equation of something raised to a power down to a solveable equation without parentheses.

(43 - 19) + (16 - 14)(4)= 24 + (2)(4)= 24 + 8= 32

yes